The effect of managerial ownership, institutional ownership, and foreign ownership on intellectual capital - Magu Oktavian; Nurmala Ahmar (Universitas Hayam Wuruk Perbanas, 2019)
This research aims to examine the effect of managerial ownership, institutional ownership, and foreign ownership on intellectual capital performance. The intellectual capital performance is measured by Extended Value Added Intellectual Capital Plus (E-VAIC Plus) which was developed by Ulum (2014). Managerial ownership is measured by the ratio of the number of stocks owned by the managers over the total company’s stocks outstanding. Institutional ownership is measured by the ratio of the number of stocks owned by institutions over the total company’s stocks outstanding. Foreign ownership is measured by the ratio of the number of stocks owned by foreign parties over the total company’s stocks outstanding. It sused a population of 34 banking companies listed on the Indonesia Stock Exchange in the period 2013-2016. They were taken using a purposive sampling technique, consisting of 20 banks. The data were analyzed using SEM-PLS. The results showed that managerial ownership has an effect on intellectual capital performance. Institutional ownership has no effect on intellectual capital performance. Foreign ownership has no effect on intellectual capital performance.